THE CHARACTERISTICS OF ALBUS DUMBLEDORE IN HARRY POTTER AND DEATHLY HOLLOW BY JK. ROWLING - Aristo, Thomas Joni Verawanto; Sijono, Sijono (Journal of English Educational Study (JEES), 2018)
Â Novel is a part of literature, a fictional piece of prose usually written in narrative style. In non-fiction novel, there are also character. The one main character is usually the non fiction maker ( author ) itself. Talked about character, there must be characteristic. The analyst tries to analysis the characteristic of Albus Dumbledore of Harry Potter and Deathly Hollow by J.K Rowling. The analyst wants to share information about the moral value of Albus Dumbledore, his dark side, his abilities, his support as a protector and helper forÂ  Harry Potter and his friends. The pupose of this study was about to describe the characteristic of Albus Dumbledore. The method of this reserach was qualitative approach with coding, decoding, categorization and confirmation. The problem of the research was used objective approach. Data collection technique was used library study and literary study. The result of this research was Albus Dumbledore is wise, gentle, kind, misterious in way, knowlegable, caring and understanding. The conclusion of this research was the character of Albus Dumbledore is not just a story but we can adapt it in our life, without magic wand, everyone can be as same as Albus Dumbledore characteristic, if there is a willing.Keyword : Character, Characteristic, Novel